Characteristics of Distribution of Heavy Metals in Rivers Around Laterite Nickel Mining Sites in the Tanggetada Area, Kolaka Regency, Southeast Sulawesi Province - Ekawati, Wahyu; Chaerul, Muhammad; Marzuki, Ismail (ASTONJADRO, 2023)
The research location is located in Tanggetada sub-district, Kolaka district, which is an area very close to laterite nickel mining sites. The determination of the research location was deliberately chosen at the nickel mining location, with the consideration that at that location the river was brownish red, and at that location there were many miners who did not carry out according to mining regulations. The method used is observational which is carried out at nickel laterite mining sites. by using a cross sectional approach that is both qualitative and quantitative. Based on the results of the data analysis that has been carried out, it can be explained that the distribution of heavy metal pollution in river water is the largest in the heavy metal Copper (Cu), namely 0.0108 mg/l, which is found at station 3, heavy metal lead (Pb), namely 0.0070 mg/l l found at station 4, heavy metal chromium (Cr) is 0.0038 found at station 6 downstream, heavy metal Cadmium (Cd) is 0.0028 mg/l found at station 3, heavy metal Hexavalent Chromium (Cr6+) is 0.0026 mg/l found at station 2. From the results of the analysis there are no heavy metals that exceed the quality standard (PP No. 82 of 2001). Meanwhile, the river sediment material produced the greatest amount of heavy metal Copper (Cu), namely 0.0229 mg/kg found at station 2, Heavy metal Cadmium (Cd), namely 0.0128 mg/kg found at station 5, Heavy metal Lead (Pb) namely 0.0177 mg /kg is found at station 1 upstream, heavy metal Chromium (Cr) is 0.0118 mg/kg found at station 6 downstream, heavy metal Hexavalent Chromium (Cr6+) is 0.0116 mg/kg found at station 6 downstream. From the results of this analysis there are no heavy metals that exceed the quality standards (USEPA, 2003).